Reliability Generalization Study of the Person-Centered Care Assessment Tool - Bru-Luna, Lluna María; Martí-Vilar, Manuel; Merino-Soto, César; Livia, José (Frontiers in Psychology, 2021)
The so-called Person-Centered Care (PCC) model identifies three fundamental principles: changing the focus of attention from the disease to the person, individualizing care, and promoting empowerment. The Person-Centered Care Assessment Tool (P-CAT) has gained wide acceptance as a measure of PCC in recent years due to its brevity and simplicity, as well as its ease of application and interpretation. The objective of this study is to carry out a reliability generalization meta-analysis to estimate the internal consistency of the P-CAT and analyze possible factors that may affect it, such as the year of publication, the care context, the application method, and certain sociodemographic properties of the study sample. The mean value of α for the 25 samples of the 23 studies in the meta-analysis was 0.81 (95% CI: 0.79–0.84), with high heterogeneity (squared-I = 85.83%). The only variable that had a statistically significant relationship with the reliability coefficient was the mean age of the sample. The results show that the P-CAT gives acceptably consistent scores when its use is oriented toward the description and investigation of groups, although it may be affected by variables such as the age of participants.